The Effect of The Number of Parking Spaces and Parking Rates on The Increase in Local Revenue Through the Potential For Parking Levies as an Intervening Variable (Study at the Batu City Transportation Agency) - Nasir, M. Jamal Abdul (The Islamic Education and Multiculturalism Foundation, 2023)
The purpose of this study is to determine and analyze the effect of the number of parking spaces and parking rates either directly or indirectly on the original regional income in Batu City. The population used in this study was all employees of the Transportation Agency and this research used a data analysis method, namely Path Analysis with SPSS software version 25. This study used instrument test, classical assumption test, f test and R² test. The results of the study are as follows: (i) The number of parking lots has a positive and significant effect on the potential parking levy. (ii) Parking Rates have a positive and significant effect on Local Revenue. (iii) The number of Parking Lots has a negative and insignificant effect on the Local Revenue. (iv) Parking Rates have a negative and insignificant effect on Local Revenue. (v) The potential for the Parking Levy to have a positive and significant effect on Local Revenue. (vi) The number of Parking Lots has a positive and significant effect on Local Revenue through the Potential Parking Levy. (vii) Parking Rates have a positive and significant effect on Local Revenue through Potential Parking Levies.